Annual report 2019: CGIAR Research Program on Policies, Institutions, and Markets - CGIAR Research Program on Policies, Institutions, and Markets (CGIAR Research Program on Policies, Institutions, and Markets, 2020)
In 2019, research conducted under the CGIAR Research Program on Policies, Institutions, and Markets (PIM) informed policies and investments of governments, development agencies, non-governmental organizations and private companies in Africa, Asia and Latin America. PIM contributed to investment plans and policies in Afghanistan, Ghana, Kenya, Nigeria, Pakistan, the Philippines and Rwanda; scaling up of digital advisory services in Ethiopia and of payments for agrobiodiversity conservation in Peru; biotechnology advances in Nigeria; renewal of community forest concessions in Guatemala; and improved rangeland governance in Ethiopia and Tanzania. At the global level, PIM research was used to shape the European Union biofuel policy as well as strategic decisions of several organizations such as the Asian Development Bank, the Bill & Melinda Gates Foundation, CGIAR, UK’s Department for International Development, the Inter-American Development Bank, the International Fund for Agricultural Development, USAID and the World Health Organization. An external review of the outcomes of PIMsupported foresight modeling work was completed.